Advancing human induced pluripotent stem cell‐derived blood‐brain barrier models for studying immune cell interactions. Issue 12 (30th October 2020) - Nishihara, Hideaki; Gastfriend, Benjamin D.; Soldati, Sasha; Perriot, Sylvain; Mathias, Amandine; Sano, Yasuteru; Shimizu, Fumitaka; Gosselet, Fabien; Kanda, Takashi; Palecek, Sean P.; Du Pasquier, Renaud; Shusta, Eric V.; et al.
Abstract: Human induced pluripotent stem cell (hiPSC)‐derived blood‐brain barrier (BBB) models established to date lack expression of key adhesion molecules involved in immune cell migration across the BBB in vivo. Here, we introduce the extended endothelial cell culture method (EECM), which differentiates hiPSC‐derived endothelial progenitor cells to brain microvascular endothelial cell (BMEC)‐like cells with good barrier properties and mature tight junctions. Importantly, EECM‐BMEC‐like cells exhibited constitutive cell surface expression of ICAM‐1, ICAM‐2, and E‐selectin. Pro‐inflammatory cytokine stimulation increased the cell surface expression of ICAM‐1 and induced cell surface expression of P‐selectin and VCAM‐1. Co‐culture of EECM‐BMEC‐like cells with hiPSC‐derived smooth muscle‐like cells or their conditioned medium further increased the induction of VCAM‐1. Functional expression of endothelial ICAM‐1 and VCAM‐1 was confirmed by T‐cell interaction with EECM‐BMEC‐like cells. Taken together, we introduce the first hiPSC‐derived BBB model that displays an adhesion molecule phenotype that is suitable for the study of immune cell interactions.